(untitled) (Bangladesh Journal of Plastic Surgery, 2011)
Oral ulcers are common, with an estimated point prevalence of 4% in the world wide. Aphthous ulcers may affect as many as 25% of the population worldwide. Patients with an oral ulcer may present initially to a general practitioner or a dental practitioner. Most ulcers are benign and resolve spontaneously but a small proportion are malignant. The incidence and prevalence of oral cancer varies across the world. Some of the highest incidences are seen in the Indian subcontinent, southern France, and South America. Importantly, the incidence of oral cancer is rising in most populations, particularly in young women. In the United Kingdom, around 2500 cases of oral cavity cancers are seen every year. Prevalence of oral lesions in population screening and survey studies shows that Candida-related and red-andwhite lesions affect 47%, denture-related 8.4%, tobacco 4.7%, oral caratotic 3.4%, carcinoma or severe dysplasia 0.2%. DOI: http://dx.doi.org/10.3329/bdjps.v1i2.8802 BDJPS 2010; 1(2): 23-29